Photosensitive resin composition for touch screen, cured film thereof, and touch screen having the cured film

By combining alkali-soluble resin containing nonpolymerizable saturated groups with a specific structure with metal oxide, photohardening forms a high refractive index layer, solving the problems of electrode pattern visibility and high refractive index layer flatness in electrostatic capacitive touch screens, and achieving efficient visual recognition and process stability.

CN112162462BActive Publication Date: 2025-04-08NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202011101671.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2014-09-30
Filing Date
2015-09-29
Publication Date
2025-04-08
Estimated Expiration
2035-09-29

AI Technical Summary

Technical Problem

When the existing touch screen uses an electrostatic capacitive structure, the electrode pattern is visible due to the difference in optical properties between the electrode pattern and the electrodeless pattern part, which reduces the visual recognition, and the color unevenness of the high refractive index layer may occur after it is formed.

Method used

A high refractive index layer is formed by photohardening to ensure the flatness and pattern formation of the layer and the like using a specific structure.

Benefits of technology

The visibility of the electrode pattern is effectively suppressed, visual recognition is improved, and flatness is maintained after the formation of the high refractive index layer, reducing the possibility of problems in the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002725580210000021
    Figure BDA0002725580210000021
  • Figure BDA0002725580210000031
    Figure BDA0002725580210000031
  • Figure BDA0002725580210000032
    Figure BDA0002725580210000032
Patent Text Reader

Abstract

The present invention provides a photosensitive resin composition for a touch screen, a cured film thereof, and a touch screen having the cured film. The photosensitive resin composition for a touch screen of the present invention contains: (A-1) an alkali-soluble resin obtained by reacting (a) a dicarboxylic acid or a tricarboxylic acid or an anhydride thereof and (b) a tetracarboxylic acid or an anhydride thereof with a reactant of an epoxy compound having two glycidyl ether groups derived from bisphenols and a monocarboxylic acid containing an unsaturated group; (B) a photopolymerizable monomer having at least one ethylenically unsaturated bond; (C) a photopolymerization initiator; (D) metal oxide particles selected from at least one of aluminum, zirconium, titanium, zinc, indium, tin, antimony and cerium; (E) a surfactant; and (F) a silane compound. The photosensitive resin composition can form a pattern by photolithography, and has particularly excellent development characteristics. The formed cured film has high transparency, and the refractive index can also be increased to prevent the pattern visibility phenomenon of the ITO wiring pattern.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application. The application number of the parent application is 201510634814.5. The application date is September 29, 2015. The title of the invention is photosensitive resin composition for touch screen and cured film thereof, and touch screen having the cured film. Technical Field

[0002] The present invention relates to a photosensitive resin composition for a touch screen, a cured film thereof, and a touch screen having the cured film. Background Art

[0003] At present, in addition to large displays such as personal computers or televisions, the demand for liquid crystal displays (LCDs) continues to expand to small and medium-sized displays such as mobile phones, smartphones, and tablet terminals. Recently, touch screens have been widely used as data input mechanisms in display devices such as these liquid crystal displays, among which electrostatic capacitive touch screens have gradually been used. The electrostatic capacitive touch screen has the following structure in the screen: on both sides of the transparent insulating film, a mosaic-shaped electrode pattern formed by transparent conductive materials such as indium tin oxide (ITO) is arranged. The two layers of electrode patterns arranged on both sides respectively show shapes connected in the x-axis direction and the y-axis direction, and are connected to the external control circuit via metal or the like to take out wiring. If a finger touches the screen, the electrostatic capacitance of the electrode pattern near it changes, and the control circuit can detect the change in the form of coordinate information and identify the position of the finger (for example, refer to patent document 1).

[0004] When the touch screen with such a structure is used in a display device such as a display, there is the following problem: the electrode pattern is visible due to the difference in optical properties between the part with the electrode pattern and the part without the electrode pattern, and the visual recognition is reduced by this so-called "pattern visible". In order to reduce the visible pattern, it is proposed to make the film thickness of the electrode pattern thinner or replace the transparent conductive material of ITO (refer to patent document 2). In addition, a method for configuring a high refractive index layer in order to reduce the difference in optical properties is proposed, but there are problems such as not having pattern formation and lack of heat resistance, and it is further expected to develop high-performance materials (refer to patent document 3, patent document 4). Furthermore, after the high refractive index layer is formed on the electrode pattern recently, the height of the part with the electrode pattern is different from the part without the electrode pattern, resulting in uneven color. Therefore, it is expected to develop a high refractive index layer forming material that can ensure the flatness of the high refractive index layer after formation even if there is a concave-convex between the electrode patterns.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2011-186717

[0008] [Patent Document 2] Japanese Patent Application Publication No. 2012-209030

[0009] [Patent Document 3] WO2013 / 038718 Manual

[0010] [Patent Document 4] Japanese Patent Application Publication No. 2013-140229 Summary of the invention

[0011] [Problems to be solved by the invention]

[0012] Therefore, the object of the present invention is to provide a photosensitive resin composition for a touch screen that can suppress the reduction of visual recognition caused by the visibility of the pattern, a cured film using the same, and a touch screen having the cured film. In addition, by using an alkali-soluble resin containing a non-polymerizable saturated group of a specific structure, the pattern forming property is excellent, which becomes an effective technology when heat resistance is required. The cured film using this technology can also be applied to an overcoat or insulating film with good heat resistance, and can therefore be used as a component of a touch screen or color filter with good heat resistance. Furthermore, the present invention provides a photosensitive resin composition for a touch screen for forming a high refractive index layer, the flatness of the high refractive index layer after formation is good, and the possibility of problems in the process after the high refractive index layer is formed can be reduced.

[0013] [Technical means to solve the problem]

[0014] The present inventors have conducted intensive research to solve the above problems, and as a result, found that by using an alkali-soluble resin containing a polymerizable unsaturated group of a specific structure and a specific metal oxide, etc., a photosensitive resin composition can be obtained that can suppress the reduction in visual recognition due to the visibility of the pattern, has excellent pattern forming properties, and can meet the requirements of heat resistance. It is also found that a photosensitive resin composition for forming a high refractive index layer with good flatness after the high refractive index layer is formed can also be obtained.

[0015] That is, the gist of the present invention is as follows.

[0016] (1) The present invention is a photosensitive resin composition for a touch screen, comprising: (A-1) an alkali-soluble resin obtained by reacting (a) a dicarboxylic acid or a tricarboxylic acid or an anhydride thereof and (b) a tetracarboxylic acid or an anhydride thereof with a reactant of an epoxy compound having two glycidyl ether groups derived from bisphenols and a monocarboxylic acid containing an unsaturated group; (B) a photopolymerizable monomer having at least one ethylenically unsaturated bond; (C) a photopolymerization initiator; (D) metal oxide particles of at least one selected from the group consisting of aluminum, zirconium, titanium, zinc, indium, tin, antimony and cerium; (E) a surfactant; and (F) a silane compound, wherein the photosensitive resin composition for a touch screen comprises 0.001% by mass to 5% by mass of the component (E), and 0.01% by mass to 20% by mass of the component (F) in the solid component that becomes a solid component after photocuring of the photosensitive resin composition.

[0017] (2) A photosensitive resin composition for a touch screen, comprising: (A-2) an alkali-soluble resin containing an unsaturated group represented by the general formula (I); (B) a photopolymerizable monomer having at least one ethylenically unsaturated bond; (C) a photopolymerization initiator; (D) metal oxide particles selected from at least one of aluminum, zirconium, titanium, zinc, indium, tin, antimony and cerium; (E) a surfactant; and (F) a silane compound, wherein the photosensitive resin composition for a touch screen comprises 0.001% by mass to 5% by mass of the component (E); and 0.01% by mass to 20% by mass of the component (F) in the solid component that becomes a solid component after light curing of the photosensitive resin composition.

[0018] [Chemistry 1]

[0019]

[0020] (Among them, R 1 represents a hydrogen atom or a methyl group; X represents a single bond or a divalent organic group having 1 to 20 carbon atoms which may contain a heteroelement inside; Y represents a tetravalent carboxylic acid residue; Z represents a hydrogen atom or a substituent represented by the following general formula (II); G represents a hydrogen atom or a substituent represented by the following general formula (III); and n represents an average value of 1 to 20);

[0021] [Chemistry 2]

[0022]

[0023] (Among them, R 1 represents a hydrogen atom or a methyl group, R 2 represents a divalent hydrocarbon group having 2 to 10 carbon atoms, L represents a divalent or trivalent carboxylic acid residue; m represents 0 or 1; p and q represent 0, 1 or 2, respectively, and p+q represents 1 or 2);

[0024] [Chemistry 3]

[0025]

[0026] (Among them, R 1 represents a hydrogen atom or a methyl group, R 2 represents a divalent hydrocarbon group having 2 to 10 carbon atoms; m represents 0 or 1).

[0027] (3) In addition, the present invention is a photosensitive resin composition for a touch screen of (1) or (2): relative to 100 parts by mass of (A-1) and / or (A-2) in the photosensitive resin composition for a touch screen, (B) is 5 parts by mass to 100 parts by mass, relative to 100 parts by mass of the total amount of (A-1) and / or (A-2) and (B), (C) is 0.1 parts by mass to 40 parts by mass, and further in the solid content (including monomer components that become solid components through photocuring reaction), (D) is 1% by mass to 60% by mass.

[0028] (4) In addition, the present invention is a photosensitive resin composition according to any one of (1) to (3), wherein the component (E) is a surfactant having a surface tension of 20 mN / m to 28 mN / m when measured with a propylene glycol monomethyl ether acetate solution having a concentration of 0.1 mass % of the component (E).

[0029] (5) The present invention is also the photosensitive resin composition according to any one of (1) to (3), wherein the component (F) is a silane compound having any functional group selected from the group consisting of an epoxy group, an oxetane group, an isocyanate group and a urea group.

[0030] (6) The present invention also provides a cured film obtained by curing the photosensitive resin composition according to any one of (1) to (5).

[0031] (7) In addition, the present invention is a touch screen having the cured film of (6).

[0032] [Effects of the Invention]

[0033] The photosensitive resin composition for a touch panel of the present invention can be patterned by photolithography, and has excellent development characteristics, and the formed cured film has high transparency and can also increase the refractive index, so that the pattern visibility of the ITO wiring pattern can be prevented, and further, a good cured film with excellent flatness after the formation of the cured film can be obtained as a transparent insulating film or protective film for a touch panel.

[0034] The touch panel of the present invention is obtained by disposing a cured film of the photosensitive resin composition for a touch panel on a mosaic-shaped electrode pattern formed of a transparent conductive material such as ITO. DETAILED DESCRIPTION

[0035] Hereinafter, the present invention will be described in detail.

[0036] The (A-1) in the photosensitive resin composition for a touch panel of the present invention is an alkali-soluble resin obtained by reacting (a) a dicarboxylic acid or a tricarboxylic acid or an anhydride thereof and (b) a tetracarboxylic acid or an anhydride thereof with a reaction product of an epoxy compound having two glycidyl ether groups derived from bisphenols and a monocarboxylic acid containing an unsaturated group. Preferably, the alkali-soluble resin is reacted in a range of 0.01 to 10 in a molar ratio of (a) / (b).

[0037] Examples of the bisphenols used as the raw material of (A-1) include bis(4-hydroxyphenyl)ketone, bis(4-hydroxy-3,5-dimethylphenyl)ketone, bis(4-hydroxy-3,5-dichlorophenyl)ketone, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxy-3,5-dimethylphenyl)sulfone, bis(4-hydroxy-3,5-dichlorophenyl)sulfone, bis(4-hydroxyphenyl)hexafluoropropane, bis(4-hydroxy-3,5-dimethylphenyl)hexafluoropropane, bis(4-hydroxyphenyl)hexafluoropropane, bis(4-hydroxyphenyl)dimethylsilane, bis(4-hydroxy-3,5-dimethylphenyl)dimethylsilane, bis(4-hydroxy-3,5-dichlorophenyl)dimethylsilane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3,5-dichlorophenyl)methane, bis(4-hydroxy-3,5-dibromophenyl)methane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)methane 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, bis(4-hydroxyphenyl)ether, bis(4-hydroxy-3,5-dimethylphenyl)ether, bis(4-hydroxy-3,5-dichlorophenyl)ether, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl) ) fluorene, 9,9-bis(4-hydroxy-3-chlorophenyl)fluorene, 9,9-bis(4-hydroxy-3-bromophenyl)fluorene, 9,9-bis(4-hydroxy-3-fluorophenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dimethylphenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dichlorophenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dibromophenyl)fluorene, 4,4'-biphenol, 3,3'-biphenol, and derivatives thereof. Among these compounds, compounds having a fluorene-9,9-diyl group can be particularly suitably used.

[0038] Then, the bisphenols are reacted with epichlorohydrin to obtain an epoxy compound having two glycidyl ether groups. The reaction is usually accompanied by oligomerization of the diglycidyl ether compound, and thus an epoxy compound of the following general formula (IV) can be obtained.

[0039] [Chemistry 4]

[0040]

[0041] Here, in the general formula (I), R 3 , R 4 , R 5 and R 6 each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom or a phenyl group, and A represents -CO-, -SO 2 -、-C(CF 3 ) 2 -、-Si(CH 3 ) 2 -、-CH 2 -、-C(CH 3 ) 2 -, -O-, fluorene-9,9-diyl or direct bond. l is an integer of 0 to 10 in each molecule. 3 , R 4 , R 5 , R 6 A is a hydrogen atom, and preferably A is fluorene-9,9-diyl. In addition, l is an integer of 1 to 10 in each molecule, and usually multiple values ​​are mixed, so the average value is 0 to 10 (not limited to integers), and the preferred average value of l is 0 to 3. If the average value of l exceeds the upper limit, when the photosensitive resin composition is prepared using the alkali-soluble resin synthesized using the epoxy compound, the viscosity of the composition becomes too large to be smoothly applied, or the alkali solubility cannot be fully imparted and the alkali developability becomes very poor.

[0042] Then, acrylic acid or methacrylic acid or both are reacted as monocarboxylic acids containing unsaturated groups with the compound of general formula (IV) to obtain a reactant having a hydroxyl group, and (a) dicarboxylic acid or tricarboxylic acid or its anhydride and (b) tetracarboxylic acid or its dianhydride are reacted with the obtained reactant having a hydroxyl group in a molar ratio (a) / (b) preferably in the range of 0.01 to 10 to obtain an alkali-soluble resin having the structure of an epoxy (meth)acrylate acid adduct represented by the following general formula (V).

[0043] [Chemistry 5]

[0044]

[0045] [Where R 3 , R 4 , R 5 and R 6 Each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom or a phenyl group, and R1 represents a hydrogen atom or a methyl group, and A represents -CO-, -SO 2 -、-C(CF 3 ) 2 -、-Si(CH 3 ) 2 -、-CH 2 -、-C(CH 3 ) 2 -, -O-, fluorene-9,9-diyl or direct bond, Y represents a tetravalent carboxylic acid residue, W each independently represents a hydrogen atom or -OC-L-(COOH)s (wherein L represents a divalent or trivalent carboxylic acid residue, and s represents an integer of 1 or 2). In addition, r is an integer of 1 to 20 in each molecule, and r represents an average value of 1 to 20]

[0046] The epoxy (meth)acrylate acid adduct (V) is an alkali-soluble resin having both an ethylenically unsaturated double bond and a carboxyl group. Therefore, as (A-1) of the photosensitive resin composition for a touch screen of the present invention, it imparts excellent photocurability, good developability, and pattern forming properties, and can obtain a good transparent cured film pattern for a touch screen.

[0047] As the (a) dicarboxylic acid or tricarboxylic acid or its anhydride used in the epoxy (meth)acrylate acid adduct of the general formula (V) of the present invention, a chain hydrocarbon dicarboxylic acid or tricarboxylic acid or its anhydride, or an alicyclic dicarboxylic acid or tricarboxylic acid or its anhydride, an aromatic dicarboxylic acid or tricarboxylic acid or its anhydride can be used. Here, the chain hydrocarbon dicarboxylic acid or tricarboxylic acid or its anhydride includes, for example, succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, diglycolic acid and the like, and further, a dicarboxylic acid or tricarboxylic acid or its anhydride into which an arbitrary substituent is introduced can be used. In addition, examples of alicyclic dicarboxylic acids or tricarboxylic acids or their anhydrides include compounds such as cyclobutanedicarboxylic acid, cyclopentanedicarboxylic acid, hexahydrophthalic acid, tetrahydrophthalic acid, and norbornanedicarboxylic acid, and further dicarboxylic acids or tricarboxylic acids or their anhydrides introduced with any substituents may be used. Furthermore, examples of aromatic dicarboxylic acids or tricarboxylic acids or their anhydrides include compounds such as phthalic acid, isophthalic acid, and trimellitic acid, and further dicarboxylic acids or tricarboxylic acids or their anhydrides introduced with any substituents may be used.

[0048] In addition, as the (b) tetracarboxylic acid or its dianhydride used in the epoxy (meth) acrylate acid adduct of the general formula (V) of (A-1) of the present invention, a chain hydrocarbon tetracarboxylic acid or its dianhydride, or an alicyclic tetracarboxylic acid or its dianhydride, or an aromatic polycarboxylic acid or its dianhydride can be used. Here, the chain hydrocarbon tetracarboxylic acid or its dianhydride includes, for example, butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, etc., and further, a tetracarboxylic acid or its dianhydride introduced with a substituent can also be used. In addition, the alicyclic tetracarboxylic acid or its dianhydride includes, for example, cyclobutane tetracarboxylic acid, cyclopentane tetracarboxylic acid, cyclohexane tetracarboxylic acid, cycloheptane tetracarboxylic acid, norbornane tetracarboxylic acid, etc., and further, a tetracarboxylic acid or its dianhydride introduced with a substituent can also be used. Furthermore, the aromatic tetracarboxylic acid or its dianhydride includes, for example, pyromellitic acid, benzophenone tetracarboxylic acid, biphenyl tetracarboxylic acid, biphenyl ether tetracarboxylic acid or its dianhydride, and further, a tetracarboxylic acid or its dianhydride introduced with a substituent can also be used.

[0049] The molar ratio (a) / (b) of the (a) dicarboxylic acid or tricarboxylic acid or its anhydride and (b) tetracarboxylic acid or its dianhydride used as the epoxy (meth)acrylate acid adduct of the general formula (V) of (A-1) of the present invention is 0.01 to 10, preferably in the range of 0.1 to 3.0. If the molar ratio (a) / (b) deviates from the above range, the optimal molecular weight cannot be obtained, and the alkali developability, heat resistance, solvent resistance, pattern shape, etc. of the photosensitive resin composition using (A-1) are deteriorated, so it is not good. In addition, the smaller the molar ratio (a) / (b), the greater the alkali solubility and the greater the molecular weight.

[0050] In addition, the epoxy (meth)acrylate acid adduct of the general formula (V) as (A-1) of the present invention preferably has a weight average molecular weight (Mw) between 2000 and 10000, and particularly preferably between 3000 and 7000. If the weight average molecular weight (Mw) is less than 2000, the adhesion of the pattern cannot be maintained during the development of the photosensitive resin composition using (A-1), resulting in pattern peeling. If the weight average molecular weight (Mw) exceeds 10000, it is easy to leave residual development residues or residual film in the unexposed part. Furthermore, (A-1) preferably has an acid value in the range of 30 mgKOH / g to 200 mgKOH / g. If the value is less than 30 mgKOH / g, alkali development of the photosensitive resin composition using (A-1) cannot be carried out smoothly, or special development conditions such as strong alkali are required. If it exceeds 200 mgKOH / g, the alkaline developer penetrates the photosensitive resin composition using (A-1) too quickly, causing stripping development, and both are undesirable.

[0051] The epoxy (meth)acrylate acid adduct of the general formula (V) used in the present invention can be produced by the above-mentioned process by a known method, for example, the method described in Japanese Patent Laid-Open No. 8-278629 or Japanese Patent Laid-Open No. 2008-9401. First, a method of reacting an unsaturated group-containing monocarboxylic acid with an epoxy compound of the general formula (IV) includes, for example, a method in which a monocarboxylic acid containing an unsaturated group in an equimolar amount with the epoxy group of the epoxy compound is added to a solvent, and in the presence of a catalyst (triethylbenzylammonium chloride, 2,6-diisobutylphenol, etc.), air is blown in while heating to 90° C. to 120° C. and stirring to react. Then, a method of reacting an acid anhydride with a hydroxyl group of an epoxy acrylate compound as a reaction product includes, for example, a method in which an epoxy acrylate compound and a predetermined amount of an acid dianhydride and an acid monoanhydride are added to a solvent, and in the presence of a catalyst (tetraethylammonium bromide, triphenylphosphine, etc.), heating and stirring at 90° C. to 130° C. are reacted.

[0052] (A-2) in the photosensitive resin composition for a touch panel of the present invention is an unsaturated group-containing alkali-soluble resin represented by the general formula (I) (hereinafter referred to as "alkali-soluble resin of the general formula (I)"). The following is a detailed description of the method for producing the alkali-soluble resin of the general formula (I).

[0053] First, an unsaturated group-containing monocarboxylic acid is reacted with an epoxy compound having two epoxy cycloalkyl groups in one molecule represented by general formula (VI), preferably (meth)acrylic acid, to obtain an epoxy (meth)acrylate compound. Examples of unsaturated group-containing monocarboxylic acid compounds include compounds obtained by reacting an acid monoanhydride such as succinic anhydride, maleic anhydride, or phthalic anhydride with acrylic acid or methacrylic acid, in addition to acrylic acid and methacrylic acid.

[0054] [Chemistry 6]

[0055]

[0056] (wherein X has the same meaning as that shown in the general formula (I))

[0057] The reaction of the epoxy compound and (meth) acrylic acid can be carried out by a well-known method, for example, using about 2 moles of (meth) acrylic acid for 1 mole of the epoxy compound having two epoxy groups. The reactant obtained by the above reaction is described in, for example, Japanese Patent Laid-Open No. 4-355450. The reactant obtained by the above reaction is a diol compound containing a polymerizable unsaturated group, which is an epoxy (meth) acrylate compound represented by the following general formula (VII).

[0058] [Chemistry 7]

[0059]

[0060] (Among them, R 1 , X has the same meaning as that shown in the general formula (I)

[0061] In the epoxy compound having two epoxy cycloalkyl groups in the molecule represented by the general formula (VI), X is a single bond or a divalent organic group having 1 to 20 carbon atoms which may contain a heteroelement inside. Examples of the divalent organic group having 1 to 20 carbon atoms which may contain a heteroelement inside include a divalent hydrocarbon group, a divalent group having a carboxyl group at one or both ends of the hydrocarbon group, and the hydrocarbon group herein may contain an ether bond-like oxygen atom or an ester bond inside. Examples of such divalent hydrocarbon groups include straight-chain hydrocarbon groups such as methylene, ethylene, propylene, isopropylidene, sec-butylene, methylisobutylene, hexylene, decylene, and dodecylene.

[0062] Specific examples of the epoxy compound having two epoxycycloalkyl groups in the molecule represented by the general formula (VI) include the epoxy compounds represented by the following general formulas (VIII) to (XIV), and two or more thereof may be used simultaneously. From the perspective of availability and the physical properties of the cured product, the epoxy compound represented by the general formula (XI) or the general formula (XII) is preferred, and preferably, g is 1, h is 5, and i is 1.

[0063] [Chemistry 8]

[0064]

[0065] (wherein, g represents an integer of 1 to 20, h represents an integer of 2 to 20, i represents an integer of 0 to 10, j represents an integer of 1 to 20, and k represents an integer of 0 to 18)

[0066] When synthesizing the epoxy (meth)acrylate compound represented by the general formula (VII), and then reacting the polycarboxylic acid or its anhydride with a monofunctional epoxy compound containing a polymerizable unsaturated group reactive with a carboxyl group to produce the alkali-soluble resin of the general formula (I), the reaction is usually carried out in a solvent using a catalyst as needed. Here, there is no particular restriction on the reaction conditions such as the solvent and catalyst used. For example, it is preferable to use a solvent having no hydroxyl group and having a boiling point higher than the reaction temperature as the main component of the reaction solvent. Such solvents are preferably cellosolve-based solvents such as ethyl cellosolve acetate and butyl cellosolve acetate, or high-boiling ether-based or ester-based solvents such as diethylene glycol dimethyl ether, ethyl carbitol acetate, butyl carbitol acetate, and propylene glycol monomethyl ether acetate, or ketone-based solvents such as cyclohexanone and diisobutyl ketone. In the reaction between the carboxyl group and the epoxy group, it is preferred to use a catalyst, and the catalyst used can be, for example, ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride, triphenylphosphine, tri(2,6-dimethoxyphenyl)phosphine, and other well-known catalysts such as phosphines. These catalysts are described in detail in Japanese Patent Laid-Open No. 9-325494.

[0067] As a second reaction, an epoxy (meth)acrylate compound (c) obtained by a reaction between an epoxy compound and (meth)acrylic acid can be reacted with an acid component (a) and an acid component (b) to obtain an alkali-soluble resin containing a polymerizable unsaturated group represented by the general formula (XV) (hereinafter referred to as "alkali-soluble resin of the general formula (XV)").

[0068] [Chemistry 9]

[0069]

[0070] (Among them, R 1 represents a hydrogen atom or a methyl group. X represents a single bond or a divalent organic group having 1 to 20 carbon atoms which may contain heteroelements inside, Y represents a tetravalent carboxylic acid residue, W independently represents a hydrogen atom or -OC-L-(COOH)s (wherein L represents a divalent or trivalent carboxylic acid residue, and s represents an integer of 1 or 2), n is an integer of 1 to 20 in each molecule, and the alkali-soluble resin of the general formula (XV) is a mixture of these. That is, n in the general formula (XV) represents an average value of 1 to 20)

[0071] The acid component used to synthesize the alkali-soluble resin of the general formula (XV) is a polybasic acid component that can react with the hydroxyl group in the epoxy (meth) acrylate compound molecule, and it is necessary to use (a) a dicarboxylic acid or a tricarboxylic acid or its acid monoanhydride and (b) a tetracarboxylic acid or its acid dianhydride in combination. These (a) dicarboxylic acid or a tricarboxylic acid or its acid monoanhydride and (b) a tetracarboxylic acid or its acid dianhydride can include the same compound group as the compound used for the epoxy (meth) acrylate acid adduct of the general formula (V).

[0072] The method for reacting the epoxy (meth)acrylate compound (c) with the acid component (a) and the acid component (b) is not particularly limited, and for example, a well-known method such as reacting an epoxy (meth)acrylate compound with tetracarboxylic dianhydride at a reaction temperature of 90° C. to 140° C. can be adopted as described in Japanese Patent Laid-Open No. 9-325494. It is desirable to react the epoxy (meth)acrylate compound (c), dicarboxylic acid or tricarboxylic acid or its acid monoanhydride (a), and tetracarboxylic dianhydride (b) in a molar ratio of (c):(a):(b)=1:0.01 to 1.0:0.2 to 1.0 so that the terminal of the compound becomes a carboxyl group. Here, if a quantitative description is given by taking the case of using (b) acid monoanhydride and (c) acid dianhydride as an example, it is desirable to react in such a manner that the molar ratio [(c) / [(a) / 2+(b)]] of the number of moles of the diol compound (epoxy (meth)acrylate compound) (c) containing a polymerizable unsaturated group to the number of moles of the amount of the acid component [(a) / 2+(b)] is 0.5 to 1.0. When the molar ratio exceeds 1.0, the content of the unreacted diol compound containing a polymerizable unsaturated group increases, which may reduce the temporal stability of the alkali-soluble resin composition. On the other hand, when the molar ratio is less than 0.5, the terminal of the alkali-soluble resin represented by the general formula (1) becomes an acid anhydride, and the content of the unreacted acid dianhydride increases, which may reduce the temporal stability of the alkali-soluble resin composition. The molar ratio of each component of (c), (a) and (b) can be arbitrarily changed within the above range for the purpose of adjusting the acid value and molecular weight of the alkali-soluble resin represented by the general formula (XV).

[0073] As a third reaction, a monofunctional epoxy compound having a polymerizable unsaturated group of the general formula (XVI) is reacted with a carboxyl group of an alkali-soluble resin of the general formula (XV) to obtain an alkali-soluble resin of the general formula (I).

[0074] [Chemistry 10]

[0075]

[0076] (Among them, R 1 represents a hydrogen atom or a methyl group, R 2represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and m is 0 or 1)

[0077] The molar ratio of the epoxy group of the unsaturated epoxy compound represented by the general formula (XVI) to the carboxyl group of the general formula (XV) can be arbitrarily changed for the purpose of adjusting the sensitivity of the photoreaction of the alkali-soluble resin represented by the general formula (I) (depending on the amount of polymerizable double bonds) or the acid value. If the molar number of the general formula (XVI) is 90% or less relative to the total molar number of the molar number of the component (a) and the molar number of the component (b), alkali developability can be imparted, and it can be used for a photosensitive resin composition with optical pattern forming properties. In addition, in the case of imparting a sensitivity-enhancing effect on the photoreaction, it must be set to 10% or more, so it is preferably 10% to 90%. Furthermore, 30% to 70% is more preferred. In addition, the acid value of the alkali-soluble resin of the general formula (I) used is preferably 20 to 180, and more preferably 30 to 120.

[0078] In addition, the weight average molecular weight (Mw) of the alkali-soluble resin of the general formula (I) of the present invention measured by gel permeation chromatography (GPC) is usually 1000 to 100000, preferably 2000 to 20000. When the weight average molecular weight is less than 1000, there is a risk of reduced adhesion of the pattern during alkali development. If the weight average molecular weight exceeds 100000, it is difficult to adjust the solution viscosity of the photosensitive resin composition suitable for coating, or alkali development requires too long a time, which is not preferred.

[0079] The photopolymerizable monomer (B) having at least one ethylenically unsaturated bond in the photosensitive resin composition for a touch screen of the present invention may be, for example, (meth)acrylates having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, or ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate. (Meth)acrylates such as glycerol (meth)acrylate, sorbitol penta (meth)acrylate, dipentaerythritol penta (meth)acrylate or dipentaerythritol hexa (meth)acrylate, sorbitol hexa (meth)acrylate, phosphazene alkylene oxide modified hexa (meth)acrylate, caprolactone modified dipentaerythritol hexa (meth)acrylate, etc.; in order to increase the refractive index of the cured product, compounds having multiple aromatic rings, such as monomers having polycyclic aromatic skeletons such as bisphenol skeletons and naphthalene skeletons, or monomers containing elements with large atomic refractive index such as S, etc., can be cited, and specifically, bisphenol A ethylene oxide diacrylate and 2,2'-bis (2-acryloyloxyethoxy) -1,1'-binaphthyl can be cited. One or more of these compounds can be used, and preferably, monomers having multiple aromatic rings or polycyclic aromatic skeletons or monomers containing elements such as S can be used. In addition, the photopolymerizable monomer having at least one ethylenically unsaturated bond is preferably a monomer having two or more photopolymerizable groups that can crosslink molecules of the alkali-soluble resin containing an unsaturated group. In addition, the photopolymerizable monomer (B) having at least one ethylenically unsaturated bond does not have a free carboxyl group.

[0080] The (C) photopolymerization initiator in the photosensitive resin composition for a touch screen of the present invention includes, for example, acetophenones such as acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminoacetophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone; benzophenones such as benzophenone, 2-chlorobenzophenone, and p-, p-bisdimethylaminobenzophenone; benzil, benzoin, benzoin methyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; 2-(o-chlorophenyl)-4,5-phenylbiimidazole, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)biimidazole, 2-(o-fluorophenyl)-4,5-diphenylbiimidazole, 2-(o-methoxyphenyl)-4,5-diphenylbiimidazole , 2,4,5-triarylbiimidazole and other biimidazole compounds, 2-trichloromethyl-5-phenylvinyl-1,3,4-oxadiazole, 2-trichloromethyl-5-(p-cyanostyryl)-1,3,4-oxadiazole, 2-trichloromethyl-5-(p-methoxyphenylvinyl)-1,3,4-oxadiazole and other halogenated methyldiazole compounds, 2,4,6-tris(trichloromethyl)-1,3,5-triazine, 2-methyl-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-phenyl-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-chlorophenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)- 1,3,5-triazine, 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-methoxyphenylvinyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(3,4,5-trimethoxyphenylvinyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-methylthiophenylvinyl)-4,6-bis(trichloromethyl)-1,3,5-triazine and other halomethyl-s-triazine compounds, 1,2-octanedione, 1-[4-(phenylthio)phenyl]-, 2-(O-benzoyl oxime), 1-(4-phenylthiophenyl)butane-1,2-dione-2-oxime-O-benzoate, 1-(4-methylthiophenyl)butane- 1,2-diketo-2-oxime-O-acetate, 1-(4-methylthiophenyl)butane-1-one oxime-O-acetate, ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyl oxime), methyl ketone, (9-ethyl-6-nitro-9H-carbazole-3-yl)[4-(2-methoxy-1-methylethoxy)-2-methylphenyl]-, O-acetyl oxime, methyl ketone, (2-methylphenyl)(7-nitro-9,9-dipropyl-9H-fluoren-2-yl)-, acetyl oxime, ethyl ketone, 1-[7-(2-methylbenzoyl)-9,9-dipropyl-9H-fluoren-2-yl]-, 1-(O-acetyl oxime), ethyl ketone, 1-(-9,O-acyl oxime compounds such as 9-dibutyl-7-nitro-9H-fluoren-2-yl)-, 1-O-acetyl oxime, benzil dimethyl ketal, sulfur compounds such as thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, anthraquinones such as 2-ethylanthraquinone, octamethylanthraquinone, 1,2-benzanthraquinone, 2,3-diphenylanthraquinone, azobisisobutyronitrile, organic peroxides such as benzoyl peroxide and cumene peroxide, thiol compounds such as 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, 2-mercaptobenzothiazole, tertiary amines such as triethanolamine and triethylamine, etc. Among them, from the viewpoint of easily obtaining a highly sensitive photosensitive resin composition, it is preferred to use O-acyl oxime compounds, and from the viewpoint of easily controlling the line width when obtaining a transparent film pattern by photolithography, it is particularly preferred to use compounds of the general formula (XVII). In addition, two or more of these photopolymerization initiators may be used. In addition, the photopolymerization initiator in the present invention is used to include a sensitizer.

[0081] [Chemistry 11]

[0082]

[0083] In formula (XVII), R 7 represents an alkyl group having 1 to 20 carbon atoms (may be straight-chain or branched, may be substituted by one or more hydroxyl groups, and may have one or more oxygen atoms in the middle of the alkyl chain. In addition, it may have a substituent such as a cycloalkyl group having 5 to 8 carbon atoms, a phenyl group, etc.), a cycloalkyl group having 5 to 8 carbon atoms, an alkanoyl group or a benzoyl group having 2 to 20 carbon atoms (may be substituted by an alkyl group having 1 to 6 carbon atoms or a phenyl group), or a phenyl group (may be substituted by an alkyl group having 1 to 6 carbon atoms, a phenyl group, or a halogen atom). In addition, R 8 represents an alkanoyl group having 2 to 12 carbon atoms (which may be substituted with one or more halogen atoms or cyano groups), an alkenoyl group having 4 to 6 carbon atoms whose double bond is not conjugated with the carbonyl group, a benzoyl group (which may be substituted with an alkyl group having 1 to 6 carbon atoms, a halogen atom or cyano group), an alkoxycarbonyl group having 2 to 6 carbon atoms, or a phenoxycarbonyl group (which may be substituted with one or more alkyl groups having 1 to 6 carbon atoms or halogen atoms). 7 is an alkyl group having 1 to 20 carbon atoms (which may be straight chain or branched, and may have a substituent such as a cycloalkyl group having 5 to 8 carbon atoms, a phenyl group, etc.), preferably R 8 It is an alkanoyl group having 2 to 12 carbon atoms (which may be substituted by one or more halogen atoms or cyano groups), or a benzoyl group (which may be substituted by an alkyl group having 1 to 6 carbon atoms, a halogen atom or a cyano group).

[0084] The (D) in the photosensitive resin composition for touch screen of the present invention is a metal oxide particle selected from at least one of aluminum, zirconium, titanium, zinc, indium, tin, antimony and cerium. Preferably, zirconium or titanium oxide can be used, and titanium oxide is particularly preferred. The shape of these metal oxide particles is not particularly limited, and particles with an average particle size of 5nm to 200nm in a dynamic scattering method (cumulant method) can be used, and 10nm to 100nm is more preferred. If it is less than 5nm, it is easy to cause aggregation and difficult to disperse uniformly, or a large amount of dispersant is required, and the desired physical properties cannot be obtained when it is made into a cured product, and the haze of the cured film exceeding 200nm is large, so it is not preferable.

[0085] The (E) in the photosensitive resin composition for a touch screen of the present invention is a surfactant having a surface tension of 20 mN / m to 28 mN / m when measured with a 0.1 mass % propylene glycol monomethyl ether acetate solution of (E), for example, a fluorine-based surfactant, a silicone-based surfactant, etc. From the perspective of ensuring the flatness after the high refractive index layer is formed even with unevenness between electrode patterns, a surfactant having a surface tension of 20 mN / m to 28 mN / m in a 0.1 mass % propylene glycol monomethyl ether acetate solution is preferred, and a fluorine-based surfactant is particularly preferred.

[0086] The (F) silane compound in the photosensitive resin composition for a touch panel of the present invention includes silane compounds of the general formula (XVIII), and specific compounds include, for example, 3-(glycidyloxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-ureidopropyltriethoxysilane, etc. From the perspective of improving the adhesion between the electrode pattern and the cured film as the high refractive index layer, ureidopropyltriethoxysilane and other silane compounds containing urea groups are preferred.

[0087] [Chemistry 12]

[0088]

[0089] (Among them, R 9 is a hydrocarbon group having 1 to 10 carbon atoms which may contain a heteroatom in the molecule, and may have a reactive group containing an unsaturated bond, an epoxy group (including an alicyclic epoxy group such as 3,4-epoxycyclohexyl group), an oxetanyl group, an isocyanate group, an amino group or a urea group as a substituent, R 10 Each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and R 11 Each independently represents an alkyl group having 1 to 4 carbon atoms, and t is 1 to 3. 9 is a hydrocarbon group having 1 to 10 carbon atoms and having an epoxy group, an oxetanyl group, an isocyanate group or a urea group as a substituent, and preferably R 10 , R11 is methyl or ethyl)

[0090] In the photosensitive resin composition of the present invention, it is preferred to use a solvent in addition to the above (A) to (F) to adjust the viscosity. Examples of the solvent include: alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 3-methoxy-1-butanol, ethylene glycol monobutyl ether, 3-hydroxy-2-butanone, diacetone alcohol, terpenes such as α-terpineol or β-terpineol, ketones such as acetone, methyl ethyl ketone, cyclohexanone, N-methyl-2-pyrrolidone, aromatic hydrocarbons such as toluene, xylene, tetramethylbenzene, cellosolve, methyl cellosolve, ethyl cellosolve, carbitol, methyl carbitol, ethyl carbitol, butyl carbitol, propylene glycol, Glycol ethers such as alcohol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, ethyl lactate, cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate; and the like can be dissolved and mixed using these solvents to prepare a uniform solution-like composition.

[0091] The photosensitive resin composition of the present invention may contain a compound having at least two epoxy groups in one molecule in order to adjust the physical properties of the cured film. Specific compounds include, for example, bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol fluorene epoxy compounds, phenol novolac epoxy compounds, cresol novolac epoxy compounds, glycidyl ethers of polyols, glycidyl esters of polycarboxylic acids, polymers containing glycidyl (meth)acrylate as units, bis(3,4-epoxycyclohexyl)methane, 2,2'-bis(3,4-epoxycyclohexyl)propane, 3,4-epoxycyclohexanecarboxylic acid (3',4'-epoxycyclohexyl)methyl ester, 1,2-ethylene-bis(3,4-epoxycyclohexyl carboxylate) , alicyclic epoxy compounds such as bis(3,4-epoxycyclohexylmethyl) adipate, multifunctional epoxy compounds having a dicyclopentadiene skeleton (e.g., HP7200 series manufactured by DIC), 1,2-epoxy-4-(2-oxacyclopropyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (e.g., "EHPE3150" manufactured by Daicel), epoxidized polybutadiene (e.g., "NISSO-PB·JP-100" manufactured by Nippon Soda Co., Ltd.), epoxy compounds having a silicone skeleton, etc. These components are preferably compounds having an epoxy equivalent of 90 g / eq to 500 g / eq and a number average molecular weight of 100 to 5000.

[0092] In addition, the photosensitive resin composition of the present invention may be mixed with additives such as a curing accelerator, a thermal polymerization inhibitor, an antioxidant, a plasticizer, a leveling agent, and a defoaming agent as needed. Examples of the thermal polymerization inhibitor and the antioxidant include hydroquinone, hydroquinone monomethyl ether, pyrogallol, tert-butylcatechol, phenothiazine, and hindered phenol compounds, and examples of the plasticizer include dibutyl phthalate, dioctyl phthalate, and tricresyl phosphate, and examples of the leveling agent or the defoaming agent include silicone, fluorine, and acrylic compounds.

[0093] Regarding the preferred composition ratio of each component of (A) to (F) in the photosensitive resin composition, relative to 100 parts by mass of (A), (B) is 5 parts by mass to 100 parts by mass, and relative to 100 parts by mass of the total amount of (A) and (B), (C) is 0.1 parts by mass to 40 parts by mass. Furthermore, in the solid component of the composition (including monomer components that become solid components through photocuring reaction), (D) is 1% by mass to 60% by mass. Furthermore, in the photosensitive resin composition (including solvent), (E) is 0.001% by mass to 5% by mass, preferably 0.001% by mass to 1.0% by mass. When (E) is less than 0.001% by mass, the concave-convex between the electrode patterns becomes larger and color unevenness may occur. In addition, when (E) exceeds 5% by mass, there is a risk of shrinkage or unevenness in the cured film. Furthermore, in the solid content of the composition (including monomer components that become solid components through photocuring reaction), (F) is 0.01% to 20% by mass, preferably 0.01% to 10% by mass. When (F) is less than 0.01% by mass, there is a particular concern about the reduction of adhesion under high temperature and high humidity. In addition, when (F) exceeds 20% by weight, there is a risk of foreign matter being generated in the cured film or the time stability of the photosensitive resin composition being reduced.

[0094] The photosensitive resin composition for a touch screen of the present invention contains the components (A) to (F) as main components. In the photosensitive resin composition solution, in the solid components (including monomer components that become solid components after photocuring) excluding the solvent, it is preferable that the total amount of the components (A) to (F) is 70% by mass or more, preferably 80% by mass, and more preferably 90% by mass or more. The amount of the solvent varies depending on the target viscosity, and is preferably in the range of 60% to 90% by mass in the photosensitive resin composition solution.

[0095] Regarding the method of using the photosensitive resin composition for a touch screen of the present invention, it can be coated and formed on a transparent conductive metal oxide film for wiring formed on a substrate such as glass or a transparent film (for example, polycarbonate, polyethylene terephthalate, polyethersulfone, etc.), and the coated film is irradiated with ultraviolet rays through a photomask to harden the exposed part, and then developed using an alkaline aqueous solution to dissolve the unexposed part to form a pattern, and post-baked. By this photolithography method, a resist pattern is formed, and it has transparency to form an insulating film between wirings, a protective film for wirings, etc.

[0096] In addition to the well-known solution dipping method and spraying method, any method such as a roll coater, a land coater, a slit coater or a rotary machine can be used to apply the photosensitive resin composition solution on the substrate. After applying to the desired thickness by these methods, the solvent is removed (pre-baked) to form a film. Pre-baking is performed by heating using an oven, a hot plate, etc. The heating temperature and heating time of pre-baking are appropriately selected according to the solvent used, for example, 1 minute to 3 minutes at a temperature of 60°C to 110°C. The film thickness of the photosensitive resin composition after pre-baking is preferably 0.1μm to 5μm. When the film thickness is less than 0.1μm, the adhesion to the substrate is reduced during alkali development in the subsequent process. On the other hand, if the film thickness exceeds 5μm, the flatness is reduced, and there is a concern that warping will occur when the substrate is a transparent film.

[0097] The exposure after pre-baking is performed by using an exposure machine, and by exposing through a photomask, only the portion of the photosensitive resin composition corresponding to the pattern is exposed to light. The exposure machine and its exposure irradiation conditions are appropriately selected, and the exposure is performed using a light source such as an ultra-high pressure mercury lamp, a high pressure mercury lamp, a metal halide lamp, and a far ultraviolet lamp, so that the photosensitive resin composition in the coating film is photocured.

[0098] Alkali development after exposure is performed to remove the unexposed portion of the photosensitive resin composition, and the desired pattern is formed by the development. The developer suitable for the alkali development includes, for example, an aqueous solution of an alkali metal or alkaline earth metal carbonate, an aqueous solution of an alkali metal hydroxide, etc., and it is particularly preferred to use a weakly alkaline aqueous solution containing 0.03% by mass to 1% by mass of a carbonate such as sodium carbonate or potassium carbonate at a temperature of 23° C. to 27° C., and a commercially available developer or ultrasonic cleaning machine can be used to accurately form a fine image.

[0099] After development in this manner, heat treatment (post-baking) is performed at a temperature of 150° C. to 250° C. for 30 minutes to 120 minutes. The post-baking is performed to obtain desired physical properties of the cured film.

[0100] [Example]

[0101] Hereinafter, the present invention will be described in more detail by means of synthesis examples and examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the evaluation of the resin in the following synthesis examples was performed as follows.

[0102] [Solid content concentration]

[0103] 1 g of the resin solution obtained in the following synthesis example was impregnated on a glass filter [weight: W 0 (g)] and weigh [W 1 (g)], based on the weight after heating at 160°C for 2 hours [W 2 (g)] and the solid content concentration was calculated by the following formula.

[0104] Solid content concentration (wt%) = 100 × (W 2 -W 0 ) / (W 1 -W 0 )

[0105] [Acid value]

[0106] The resin solution obtained in the following synthesis example was dissolved in dioxane and titrated with a 1 / 10 N-KOH aqueous solution using a potentiometric titrator [trade name COM-1600 manufactured by Hiranuma Sangyo Co., Ltd.], and the amount of KOH required per 1 g of solid content was taken as the acid value.

[0107] [Molecular weight]

[0108] The molecular weight was measured using a gel permeation chromatography (GPC) [HLC-8220GPC manufactured by Tosoh Co., Ltd., solvent: tetrahydrofuran, column: TSK gel Super H-2000 (2 columns) + TSK gel Super H-3000 (1 column) + TSK gel Super H-4000 (1 column) + TSK gel Super-H 5000 (1 column) [manufactured by Tosoh Co., Ltd.], temperature: 40°C, rate: 0.6 ml / min], and the molecular weight is a value obtained by calculating the weight average molecular weight (Mw) as a value converted to standard polystyrene [PS-oligomer set manufactured by Tosoh Co., Ltd.].

[0109] [Surface tension]

[0110] The surface tension of a propylene glycol monomethyl ether acetate solution having a surfactant concentration of 0.1 mass % was measured under the conditions of an air temperature of 23° C. and a humidity of 50% using a plate method automatic surface tensiometer (Model: CBVP-Z manufactured by Kyowa Interface Science Co., Ltd.).

[0111] [Synthesis example 1]

[0112] In a 500 ml four-necked flask with a reflux condenser, 0.23 mol of a bisphenol fluorene epoxy compound, 0.46 mol of acrylic acid, 161.0 g of propylene glycol monomethyl ether acetate and 0.48 g of tetraethylammonium bromide (TEAB) were added, and the mixture was stirred under heating at 100°C to 105°C for 20 hours to react. Then, 0.08 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 0.18 mol of 1,2,3,6-tetrahydrophthalic anhydride were added to the flask, and the mixture was stirred under heating at 120°C to 125°C for 6 hours to obtain an alkali-soluble resin solution 1 represented by the general formula (V). The solid content concentration of the obtained resin solution was 55.6 wt%, the acid value (solid content conversion) was 101 mgKOH / g, and the Mw obtained by GPC analysis was 2400.

[0113] In addition, the bisphenol fluorene epoxy compound used is a compound of the general formula (IV), wherein A is fluorene-9,9-diyl, R 3 ~R 6 The same compound was used in Synthesis Examples 2 and 3.

[0114] [Synthesis example 2]

[0115] 0.23 mol of bisphenol fluorene epoxy compound, 0.46 mol of acrylic acid, 161.0 g of propylene glycol monomethyl ether acetate and 0.48 g of tetraethylammonium bromide (TEAB) were added to a 500 ml four-necked flask with a reflux condenser, and the mixture was stirred under heating at 100°C to 105°C for 20 hours to react. Then, 0.12 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 0.12 mol of 1,2,3,6-tetrahydrophthalic anhydride were added to the flask, and the mixture was stirred under heating at 120°C to 125°C for 6 hours to obtain an alkali-soluble resin solution 2 represented by the general formula (V). The solid content concentration of the obtained resin solution was 55.6 wt %, the acid value (solid content conversion) was 103 mgKOH / g, and the Mw obtained by GPC analysis was 3600.

[0116] [Synthesis example 3]

[0117] 0.23 mol of bisphenol fluorene epoxy compound, 0.46 mol of acrylic acid, 156.0 g of propylene glycol monomethyl ether acetate and 0.48 g of tetraethylammonium bromide (TEAB) were added to a 500 ml four-necked flask with a reflux condenser, and the mixture was stirred under heating at 100°C to 105°C for 20 hours to react. Then, 0.15 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 0.005 mol of 1,2,3,6-tetrahydrophthalic anhydride were added to the flask, and the mixture was stirred under heating at 120°C to 125°C for 6 hours to obtain an alkali-soluble resin solution 3 represented by the general formula (V). The solid content concentration of the obtained resin solution was 55.6 wt%, the acid value (solid content conversion) was 93 mgKOH / g, and the Mw obtained by GPC analysis was 8300.

[0118] [Synthesis Example 4]

[0119] 0.34 mol of 3,4-epoxycyclohexylmethyl (3,4-epoxy) cyclohexanecarboxylate, 0.68 mol of acrylic acid, 139.0 g of propylene glycol monomethyl ether acetate and 2.15 g of tetraethylammonium bromide (TEAB) were added to a 500 ml four-necked flask equipped with a reflux condenser, and stirred for 20 hours under heating at 100°C to 105°C. Then, 0.12 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 0.27 mol of 1,2,3,6-tetrahydrophthalic anhydride were added to the flask, and stirred for 8 hours under heating at 120°C to 125°C. Furthermore, 0.28 mol of glycidyl methacrylate was added, and stirred for 8 hours under heating at 100°C to 105°C to obtain an alkali-soluble resin solution 4. The obtained resin solution had a solid content concentration of 57.0 wt %, an acid value (based on solid content) of 82 mgKOH / g, and an Mw of 3,500 as determined by GPC analysis.

[0120] [Comparative Synthesis Example 1]

[0121] In a 1000 ml four-necked flask equipped with a nitrogen inlet tube and a reflux tube, 51.65 g (0.60 mol) of methacrylic acid, 38.44 g (0.38 mol) of methyl methacrylate, 38.77 g (0.22 mol) of benzyl methacrylate, 5.91 g of azobisisobutyronitrile and 370 g of diethylene glycol dimethyl ether were added, and the mixture was stirred for 8 hours at 80° C. to 85° C. under a nitrogen stream to polymerize. Furthermore, 39.23 g (0.28 mol) of glycidyl methacrylate, 1.44 g of triphenylphosphine and 0.055 g of 2,6-di-tert-butyl-p-cresol were added to the flask, and the mixture was stirred for 16 hours at 80° C. to 85° C. to obtain an alkali-soluble resin solution 5. The obtained resin solution had a solid content concentration of 32% by mass, an acid value (based on solid content) of 110 mgKOH / g, and an Mw of 18,100 as determined by GPC analysis.

[0122] (Preparation of photosensitive resin composition)

[0123] The photosensitive resin compositions of Examples 1 to 11 and Comparative Examples 1 to 7 were prepared by mixing according to the compositions shown in Tables 1 and 2. The components used for mixing are as follows.

[0124] Alkali-soluble resin solutions 1 to 5: Alkali-soluble resin solutions obtained in Synthesis Examples 1 to 4 and Comparative Synthesis Example 1

[0125] Photopolymerizable monomers

[0126] Photopolymerizable monomer 1: A mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate [trade name DPHA manufactured by Nippon Kayaku Co., Ltd.]

[0127] Photopolymerizable monomer 2: 2,2'-bis(2-acryloyloxyethoxy)-1,1'-binaphthyl

[0128] Photopolymerization initiator: 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyl oxime)] [trade name Irgacure OXE01 manufactured by BASF]

[0129] Metal oxide dispersion: Titanium oxide dispersion in propylene glycol monomethyl ether acetate solvent with a titanium oxide concentration of 19.6 mass % and a dispersant of 9.3 mass % (average particle size of titanium oxide by cumulative weight method: 62 nm)

[0130] Solvent

[0131] Solvent 1: Propylene glycol monomethyl ether acetate (PGMEA)

[0132] Solvent 2: Diethylene glycol methyl ethyl ether

[0133] Surfactants

[0134] Surfactant 1: A 1% by mass solution of polyether-modified polydimethylsiloxane [BYK 302 manufactured by BYK Chemie Japan] diluted 100 times with PGMEA (the surface tension of a PGMEA solution having a polyether-modified polydimethylsiloxane concentration of 0.1% by mass was 25.9 mN / m)

[0135] Surfactant 2: A 1 mass % solution of a perfluoroalkyl group-containing oligomer [F-477 manufactured by DIC Corporation] diluted 100 times with PGMEA (the surface tension of a PGMEA solution having a perfluoroalkyl group-containing oligomer concentration of 0.1 mass % was 27.0 mN / m)

[0136] Silane coupling agent

[0137] Silane coupling agent 1: 3-glycidyloxypropyltrimethoxysilane

[0138] Silane coupling agent 2: 3-ureidopropyltriethoxysilane

[0139] [Table 1]

[0140]

[0141] [Table 2]

[0142]

[0143] *Add 100% surfactant. (Not diluted 100 times with solvent)

[0144] The evaluation methods for evaluating various properties using the photosensitive resin composition solutions of Examples 1 to 11 and Comparative Examples 1 to 7 are shown below, and the evaluation results are shown in Tables 3 and 4.

[0145] (Transmittance and refractive index)

[0146] The photosensitive resin composition solution was applied to a degreased and cleaned glass substrate with a thickness of 1.2 mm and a size of 125 mm × 125 mm using a spin coater under the condition that the dry film thickness became 1.0 μm, and after drying, it was irradiated with ultraviolet light of 10 mW / cm2 at a wavelength of 365 nm for 10 seconds using a 500 W high pressure mercury lamp without using a photomask. After exposure, it was developed with a 0.4% sodium carbonate aqueous solution at a pressure of 0.1 MPa at 23°C for 60 seconds, and then heat-cured at 230°C for 30 minutes using a hot air dryer. The transmittance and refractive index of the glass substrate formed with the cured film were evaluated.

[0147] The transmittance was measured at 400 nm using a spectrophotometer (device: Nippon Denshoku SD5000). ○: 85% or more, ×: less than 85%

[0148] The refractive index was measured for light of 633 nm using a prism coupler film thickness refractometer (Model 2010 / M manufactured by Metricon).

[0149] (Developability)

[0150] The photosensitive resin composition solution was applied to a degreased and cleaned ITO film-forming glass substrate with a thickness of 1.2 mm and a size of 125 mm × 125 mm using a spin coater under the condition that the dry film thickness was 1.0 μm, and after drying, a photomask having a predetermined range of L / S (line width / space width) was brought into close contact, and irradiated with a wavelength of 365 nm and an illumination of 10 mW / cm using a 500 W high pressure mercury lamp. 2 After exposure, the unexposed portion of the coating film was removed by developing with a 0.4% sodium carbonate aqueous solution at 23°C and a pressure of 0.1 MPa for 60 seconds, and then heat-hardening treatment was performed at 230°C for 30 minutes using a hot air dryer.

[0151] The formation of thin lines of the formed resist film pattern was confirmed using a microscope and evaluated as follows.

[0152] ○: A pattern with L / S of 15 μm / 15 μm or more is formed without residue

[0153] ×: A pattern with L / S less than 15 μm / 15 μm is not formed, or burrs or residues of the pattern are conspicuous

[0154] (ITO pattern can be seen in the evaluation)

[0155] On an ITO film-forming glass substrate of 1.2 mm thick and 125 mm × 125 mm in size, a 3 mm wide polyimide tape is attached in a stripe shape to form a 3 mm interval. Then, after being immersed in a glass dish (schale) added with aqua regia at room temperature for 2 minutes, it is washed with pure water, and the ITO film on the part where the polyimide tape is not attached is removed, and then the polyimide tape is peeled off to form a striped ITO pattern. On the glass substrate formed with the striped ITO pattern, a photosensitive resin composition solution is applied on the glass substrate using a spin coater under the condition that the dry film thickness becomes 1.0 μm and dried, and then a photomask with a predetermined range of L / S (line width / space width) is brought into close contact, and a 500 W high-pressure mercury lamp is used to irradiate with an illumination of 10 mW / cm at a wavelength of 365 nm. 2After exposure, the unexposed portion of the coating was removed by developing with a 0.4% sodium carbonate aqueous solution at a pressure of 0.1 MPa for 60 seconds at 23°C, and then heat-curing treatment was performed at 230°C for 30 minutes using a hot air dryer to form a cured film in the exposed portion. In the glass substrate with an ITO stripe pattern on which the cured film was formed, the cured film-forming portion and the non-forming portion were compared by visual inspection to evaluate whether the ITO pattern can be confirmed in the non-forming portion but the ITO pattern is also visible in the forming portion (the pattern is visible), or the ITO pattern is not visible in the forming portion (no pattern is visible).

[0156] ○: The ITO pattern is not noticeable due to the cured film, and no pattern is visible.

[0157] ×: Even with the presence of a cured film, the ITO pattern is conspicuous and the pattern is clearly visible

[0158] (Uneven color)

[0159] On an ITO film-forming glass substrate of 1.2 mm thick and 125 mm × 125 mm in size, a 3 mm wide polyimide tape is attached in a stripe shape to form a 3 mm interval. Then, after being immersed in a glass dish added with aqua regia for 2 minutes at room temperature, it is washed with pure water to remove the ITO film on the part where the polyimide tape is not attached, and then the polyimide tape is peeled off to form a striped ITO pattern. On the glass substrate formed with the striped ITO pattern, a photosensitive resin composition solution is applied using a spin coater under the condition that the dry film thickness becomes 1.0 μm and dried, and then, without using a photomask, a 500 W high-pressure mercury lamp is used to irradiate with an illumination of 10 mW / cm at a wavelength of 365 nm. 2 After exposure, the unexposed portion of the coating was removed by developing with a 0.4% sodium carbonate aqueous solution at a pressure of 0.1 MPa at 23°C for 60 seconds, and then heat-curing treatment was performed at 230°C for 30 minutes using a hot air dryer to form a cured film of the exposed portion. In the glass substrate with an ITO stripe pattern on which the cured film was formed, the color unevenness caused by the unevenness between the ITO patterns was evaluated by visual inspection.

[0160] ◎: No color unevenness was observed

[0161] ○: Color unevenness is observed in an area less than 1 / 4 of the glass substrate with the ITO stripe pattern

[0162] △: Color unevenness is observed in an area less than 1 / 3 of the glass substrate with an ITO stripe pattern.

[0163] ×: Color difference is observed on the entire surface of the glass substrate with the ITO stripe pattern, or shrinkage and unevenness occur in the cured film

[0164] (Moisture resistance reliability)

[0165] The photosensitive resin composition solution was applied to a degreased and cleaned glass substrate with a thickness of 1.2 mm and a size of 125 mm×125 mm using a spin coater at a dry film thickness of 1.0 μm and dried. Then, without using a photomask, a 500 W high pressure mercury lamp was used to illuminate the substrate at a wavelength of 365 nm with an illumination of 10 mW / cm 2 Irradiate with ultraviolet light for 10 seconds. After exposure, develop with 0.4% sodium carbonate aqueous solution at 23°C at a pressure of 0.1MPa for 60 seconds, and then use a hot air dryer to heat and harden at 230°C for 30 minutes. The glass substrate on which the cured film was formed was placed at a temperature of 121°C, a humidity of 100%, and an air pressure of 2atm for 5 hours. Then, a tape peeling test was carried out, that is, the hardened material was placed using a Super Cutter Guide manufactured by Taiyou Machinery Co., Ltd., and cuts were made in a manner to form a grid of 100 1mm×1mm squares, and a cellophane tape (manufactured by Nichiban) was attached to the grid and then peeled off.

[0166] ◎: The hardened material in the mesh is not peeled off at all

[0167] ○: Less than 1 / 4 of the hardened material in the mesh peeled off

[0168] △: Less than 1 / 3 of the hardened material in the mesh peels off

[0169] ×: 1 / 3 or more peeled off, or foreign matter was generated, or the stability of the photosensitive resin composition over time was deteriorated

[0170] (Resistance to heat discoloration)

[0171] The photosensitive resin composition solution was applied on a degreased and cleaned glass plate having a thickness of 1.2 mm using a spin coater to a dry film thickness of 1.2 μm and dried. The entire surface of the glass plate having the white film formed thereon as described above was irradiated with a 500 W high pressure mercury lamp at a wavelength of 365 nm and an illumination of 10 mW / cm without using a photomask. 2After exposure, the developer was treated with a 0.4% sodium carbonate aqueous solution at 23°C and a pressure of 0.1 MPa for 60 seconds. Then, a heat curing treatment was performed at 230°C for 30 minutes using a hot air dryer. In order to confirm the heat discoloration resistance, a heat treatment was further performed at 230°C for 150 minutes, and the yellowness was measured using a spectrophotometer (device: Nippon Denshoku SD5000).

[0172] [Table 3]

[0173]

[0174] [Table 4]

[0175]

[0176] As shown by the results of Examples 1 to 11, when a cured film is formed on an ITO pattern using the photosensitive resin composition of the present invention, it is known that the cured film has alkali-developable pattern formation for forming a desired pattern, and a cured film having pattern visibility without an ITO pattern, excellent color unevenness and moisture resistance reliability, and excellent heat discoloration resistance can be obtained. If the specific alkali-soluble resin of the present invention is not used as in Comparative Example 1, although the pattern formation is excellent and a cured film having pattern visibility without an ITO pattern can be obtained by increasing the refractive index, the yellowness after heating at 230°C for 180 minutes exceeds 1, and only a cured film with poor heat discoloration resistance can be obtained. In addition, if a metal oxide for the purpose of high refraction is not added as in Comparative Example 2, although the pattern formation and heat discoloration resistance are sufficient, the refractive index cannot be sufficiently increased, and the pattern visibility of the ITO pattern cannot be eliminated. In addition, it is known that when the surfactant or silane compound in the photosensitive resin composition of the present invention exceeds the predetermined range, as in Comparative Examples 4 to 7, the color unevenness and moisture resistance reliability are respectively reduced.

[0177] [Industrial Applicability]

[0178] The photosensitive resin composition of the present invention can suppress the reduction of visual recognition caused by the visible pattern of the transparent conductive oxide pattern such as ITO, and is also excellent in pattern formation, color unevenness, moisture resistance reliability, and heat discoloration resistance, so it is useful as an insulating film or protective film of a touch screen. In addition, it is also useful as an outer coating or insulating film with good pattern formation or heat resistance, and is particularly useful when it is intended to be formed in the form of a thin film because a high refractive index can be achieved, and can be used as a component of a display device such as a color filter.

Claims

1. A photosensitive resin composition for a touch screen, characterized in that: contain: (A-1) an alkali-soluble resin obtained by reacting (a) a dicarboxylic acid or a tricarboxylic acid or an anhydride thereof and (b) a tetracarboxylic acid or an anhydride thereof with a reactant of an epoxy compound having two glycidyl ether groups derived from bisphenols and a monocarboxylic acid containing an unsaturated group; (B) a photopolymerizable monomer having at least one ethylenically unsaturated bond; (C) a photopolymerization initiator; (D) titanium oxide particles; (E) a surfactant; and (F) a silane compound, wherein: The component (A-1) is represented by the general formula (V) and is reacted at a ratio of (a) / (b) of 0.01 to 3.0, has a weight average molecular weight of 2000 to 10000, and an acid value of 30 mgKOH / g to 200 mgKOH / g. The photosensitive resin composition contains 0.001% to 5% by mass of a component (E), and the photosensitive resin composition contains 0.01% to 0.1% by mass of a component (F) in a solid component after photocuring. In the formula, R3, R4, R5 and R6 independently represent a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom or a phenyl group, R1 represents a hydrogen atom or a methyl group, A represents a fluorene-9,9-diyl group, Y represents a tetravalent carboxylic acid residue, and W independently represents a hydrogen atom or -OC-L-(COOH)s, wherein L represents a divalent or trivalent carboxylic acid residue, and s represents an integer of 1 or 2; in addition, r is an integer of 1 to 20 in each molecule, and r represents an average value of 1 to 20.

2. The photosensitive resin composition for a touch screen according to claim 1, characterized in that: The component (F) is a silane compound having a urea group.

3. The photosensitive resin composition for a touch screen according to claim 1 or 2, characterized in that: The component (E) is a surfactant having a surface tension of 20 to 28 mN / m when measured as a propylene glycol monomethyl ether acetate solution having a concentration of 0.1% by mass of the component (E).

4. The photosensitive resin composition for a touch screen according to claim 1 or 2, characterized in that: Relative to 100 parts by mass of component (A-1), the amount of component (B) is 5 to 100 parts by mass; relative to 100 parts by mass of the total amount of components (A-1) and (B), the amount of component (C) is 0.1 to 40 parts by mass; in the solid content, the amount of component (D) is 1% to 60% by mass.

5. A hardened film, characterized in that: The photosensitive resin composition for a touch panel according to any one of claims 1 to 4 is cured.

6. A touch screen, characterized in that: A cured film according to claim 5 is provided.

Citation Information

Patent Citations

  • Resin composite, solder resist resin composite, and hardened materials thereof

    JP1992355450A

  • Composition for forming light-shielding thin film and light-shielding film formed using the composition

    JP1996278629A

  • Alkali development unsaturated resin component and highly sensitive negative type pattern formation material using the same

    JP1997325494A

  • Resist composition for color filter, method for producing the same, and color filter using the same

    JP2008009401A

  • Capacitive touch panel and method of manufacturing the same

    JP2011186717A